Effect of Initial Substrate pH and Light Intensity on Biohydrogen Production through photo-fermentation from Palm Oil Mill Effluent (POME) - Furqon Furqon; Yohanes Aris Purwanto; Radite Setiawan; Bambang Susilo (Journal of Renewable Energy and Environment)
The Palm Oil Mill Effluent (POME) still contains a significant quantity of organic substances that can potentially serve as raw materials for biohydrogen production. This research explores the influence of initial substrate pH and light intensity on the conversion of POME into biohydrogen through photo-fermentation. The study begins by analyzing certain characteristics of POME that may have an impact and identifying indigenous bacteria present in the substrate. The initial substrate pH (neutralized and unaltered) and light intensity (7000 lux and 9500 lux) are tested in combination. A modified Gompertz equation is used to analyze the kinetics of biohydrogen production. The substrate pH neutralization and 9500 lux light intensity resulted in the highest yields and production rates, with values of 516.18 mL-H2/L-POME, 7.17 mL-H2/L-POME/hour, and 2.14% Light Conversion Efficiency (LCE). Changes in ORP (Oxidation-Reduction Potential) values during the treatments indicated an inverse relationship with biohydrogen production. Simulation results and data fitting using the modified Gompertz model yielded excellent coefficients of determination for all treatment data, exceeding 0.99.